2020
DOI: 10.21315/aamj2020.25.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis on Employee Wellbeing: The Roles of Authentic Leadership, Rewards, and Meaningful Work

Abstract: Employee wellbeing (EW) is becoming a genuine concern, and it has seen a resurgence in interest with the challenges in light of industrial revolution and globalisation. There is no doubt that wellbeing of the employees is one of the secret recipes that generates high return value for all levels of chains; the individual and the organisational productivity and growth as well as nation’s prosperity. However, majority of leadership researchers have failed to capture the multi-dimensional concept of EW. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The research also found that total reward systems have a significant influence on employee well-being. This is consistent with previous research indicating that total reward systems serve as a tool to motivate employees to increase productivity and have a positive impact on employee well-being (Gbande, 2016;Hulkko-Nyman et al, 2014;Salleh et al, 2020). The study emphasizes the necessity of aligning total reward systems with the changing work styles brought about by digital transformation.…”
Section: H7dsupporting
confidence: 91%
“…The research also found that total reward systems have a significant influence on employee well-being. This is consistent with previous research indicating that total reward systems serve as a tool to motivate employees to increase productivity and have a positive impact on employee well-being (Gbande, 2016;Hulkko-Nyman et al, 2014;Salleh et al, 2020). The study emphasizes the necessity of aligning total reward systems with the changing work styles brought about by digital transformation.…”
Section: H7dsupporting
confidence: 91%
“…Previous studies confirmed partial direct relationships between the variables, such as RS and JS (Valaei and Rezaei, 2016), RS and motivation (Martono et al. , 2018), leadership and rewards (Salleh et al. , 2020), leadership and JS (Paais and Pattiruhu, 2020), or motivation and JS (Pham et al.…”
Section: Introductionmentioning
confidence: 65%
“…These results are important for practitioners and firm's managers since they provide some specific guidelines for the successful implementation of human resources practices. Previous studies confirmed partial direct relationships between the variables, such as RS and JS (Valaei and Rezaei, 2016), RS and motivation (Martono et al, 2018), leadership and rewards (Salleh et al, 2020), leadership and JS (Paais and Pattiruhu, 2020), or motivation and JS (Pham et al, 2021). We didn't found previous research who have studied structurally any of the mediating effects that we purpose.…”
Section: Introductionmentioning
confidence: 68%
“…The higher the similarity between two items, the higher the weight of the squared distance in the sum. The next process involves translation, rotation and reflection of the map to obtain optimal visual results (Siswanto et al, 2021;Salleh et al, 2020). 79 This research aims to conduct a survey and test bibliometric performance indicators to understand some determining factors in the reward domain.…”
Section: Distribution Analysis -Results Obtainedmentioning
confidence: 99%